Current State Of Talent Development Of Talented Students Based On Biological Sciences (Problem Teaching Technology) - Guljahon Uchqunovna Suyunova (Euro Asian Journal Publishing, 2024)
This work presents information about the methods and possibilities of using pedagogical technologies in the teaching of biology. The role of technology in the development of talent of gifted students based on biological science is highlighted.
Keywords: Pedagogical technology; conceptual; procedural